ANALISIS KEMAMPUAN BERBICARA ANAK AUTIS (AN ANALYSIS OF AUTISTIC CHILD’S SPEAKING ABILITY) - Latifah Fitriana Sekarsari; Achmad Wahidy; Barkudin Barkudin (Metalingua: Jurnal Penelitian Bahasa, 2021)
AbstractThis study aims to determine the speaking ability of children with autism in communication. The method used is descriptive qualitative with data collection techniques, observation, interviews, and documentation that occurred in the field with the conversation recording technique. The data obtained by the researcher were then analyzed using Scovel's theory of the four stages of language production by humans during communication, conceptualization, formulation, articulation, and self-monitoring. From the data that has been analyzed, it is found that R's speaking ability can be said to be good, because of the four stages of language production, R is able to pass 3 stages well, first is conceptualizing the utterance he will say, also being able to respond to questions and words from people around him, then pronunciation of R in speaks quite well even though using a dialect of English, and R is able to find out mistakes in pronunciation with the help of people around him.